Monitoring of Salinity, Temperature, and Drought Stress in Grafted Watermelon Seedlings Using Chlorophyll Fluorescence - Shin, Yu Kyeong; Bhandari, Shiva Ram; Lee, Jun Gu (Frontiers in Plant Science, 2021)
Chlorophyll fluorescence (CF) is used to measure the physiological status of plants affected by biotic and abiotic stresses. Therefore, we aimed to identify the changes in CF parameters in grafted watermelon seedlings exposed to salt, drought, and high and low temperatures. Grafted watermelon seedlings at the true three-leaf stage were subjected to salinity levels (0, 50, 100, 150, and 200 mM) and temperature [low (8 °C), moderate (24 ºC), and high (40 °C)] stresses for 12 days under controlled environmental conditions independently. Eight CF parameters were measured at 2-day intervals using the FluorCam machine quenching protocol of the FluorCam machine. The seedlings were also exposed to drought stress for three days independent of salinity and temperature stress; CF parameters were measured at one-day intervals. In addition, growth parameters, proline, and chlorophyll content were evaluated in all three experiments. The CF parameters were differentially influenced depending on the type and extent of the stress conditions. The results showed a notable effect of salinity levels on CF parameters, predominantly in maximum quantum yield (Fv/Fm), non-photochemical quenching (NPQ), the ratio of the fluorescence decrease (Rfd), and quantum yield of non-regulated energy dissipation in PSII [Y(NO)]. High temperature had significant effects on Rfd and NPQ, whereas low temperature showed significant results in most CF parameters: Fv/Fm, Y(NO), NPQ, Rfd, the efficiency of excitation capture of open photosystem II (PSII) center (Fv′/Fm′), and effective quantum yield of photochemical energy conversion in PSII [Y(PSII)]. Only NPQ and Rfd were significantly influenced by severe drought stress. Approximately all growth parameters were significantly influenced by the stress level. Proline content increased with an increase in stress levels in all three experiments, whereas the chlorophyll (a and b) content either decreased or increased depending upon the stressor. The results provided here may be useful for understanding the effect of abiotic stresses on CF parameters and the selection of index CF parameters to detect abiotic stresses in grafted watermelon seedlings.